EXPLORATION OF AUGMENTED REALITY AND VIRTUAL REALITY IN THE RETAIL INDUSTRY - et. al., Thanda Chandan (International Journal of Modern Agriculture, 2021)
Augmented Reality (AR) is a technology that integrates the real and virtual world with information through digital media. It encapsulates the real world and the digital world by showing how they intersect and interact with the global world. Virtual technology, as a modern form of contact with the actual environment, incorporates sensory features such as simulated representations or sound effects, sounds, or feelings. On the other hand, virtual reality creates and pulls apart a computer-generated world. Advertising, locations, incentives, and discounts are essential factors of this system in the context of AR / VR integration, personalization, communication, adoption, experience with users, and privacy. In the retail sectors, the combined analysis of AR and VR needs to be quite relevant. The new COVID 19 scenario has rendered it better than current retail schemes, especially in e-commerce. On comparing with the traditional system for retailing the new AR and VR based application very much convincing. This current COVID 19 scenario has also rendered it better than established retail structures, especially in e-commerce. Such emerging trends can affect how consumers select platforms, select products, and make purchasing decisions. The real and synthetic worlds are already mixing. In these two parallels, what is unique and comparable is how innovations will influence each other and therefore determine the future of retail business. Changes would potentially benefit individuals with good judgment or increase trust and confidence with their purchase decisions. Retailers will also consider these current and upcoming trends that help keep their buyers more and more drawn that shops (both online and offline) while promoting their own lives as retailers. This paper discussed different dimensions and opportunities of AR and VR using secondary research that implies the changing trend towards newer technologies. The research also highlights the advantages of retail companies by implementing AR and VR systems to improve sales and maintenance in the existing system properly. This article examined different aspects of AR with VR and its prospects, especially in terms of revenue growth worldwide. Study shows that the ever-growing segment of the consumer sector is an integral part of the economy. It is high time to build on the evolving retail fusing modern technology to help consumers make purchase decisions. This article has presented how Augmented reality and Virtual reality come into play to change the retail industry’s current trend.